THE RELATIONSHIP BETWEEN EXPOSURE VIOLENCE TO ADOLESCENT AGGRESIVE BEHAVIOR IN GUNUNG PUTRI 1 JUNIOR HIGH SCHOOL BOGOR: HUBUNGAN PAPARAN TAYANGAN KEKERASAN DENGAN PERILAKU AGRESIF REMAJA DI SMP N 1 GUNUNG PUTRI KABUPATEN BOGOR - Satrio Satrio Kusumo Lelono (Wijaya Husada, 2019)
Background : Aggressive behavior is a way to fight very strongly, fight, injure, attack, kill or punish others, aggressively intended to hurt others or damage other people's property. Aggressive behavior aims to hurt others, both physically and psychologically, aggressive behavior can be done verbally or physically. Watching violence shows influence violent behavior, especially in school children. The more often children watch violent shows, the children will tend to be more aggressive and more violent. Violent impressions can also cause children to lose their sense of sensitivity. That is, they consider violence to be something normal and normal. As a result, they become accustomed to violence in everyday life. Objective :Determining the correlation between violence exposure with aggressive behavior of adolescent in Gunung Putri Junior High School Bogor Dstrict. Method :Research design used is Deskriptif Analitik Kuantitatif with Cross Sectional approach. The population studied were all students of Gunung Putri Junior High School Bogor Dstrict amounted to 926 students, after Slovin calculated using the formula obtained a sample of 279 students with the sampling technique is Random Sampling. Result : From the 279 respondents were shown that students who have aggressive behavior are often exposed to violent exposure were reached 87 respondents (31.2%) that are greater than students who have aggressive behavior and are rarely exposed to violent exposure as many as 58 respondents (20.8%). Values obtained P value= 0,001 with significant value was ≤ 0,05 , so that Ha is accepted, and obtained the value CC=0,200 that’s meaning there was strong relation between violence exposure and aggressive behavior. Conclussion :There was relatioship between violence exposure with aggressive behavior of adolescent in Gunung Putri Junior High School Bogor in 2017. The researcher were Expected that the results of this study can be used as information for the school and especially counselour teacher in making efforts to gap them, then guide and prevent the aggressive behavior in schools.